Calpain proteolytic systems counteract endothelial cell adaptation to inflammatory environments - Takuro Miyazaki; Risako Akasu; Akira Miyazaki (BMC, 2020)
Abstract Vascular endothelial cells (ECs) make up the innermost surface of arteries, veins, and capillaries, separating the remaining layers of the vessel wall from circulating blood. Under non-inflammatory conditions, ECs are quiescent and form a robust barrier structure; however, exposure to inflammatory stimuli induces changes in the expression of EC proteins that control transcellular permeability and facilitate angiogenic tube formation. Increasing evidence suggests that dysfunction in intracellular proteolytic systems disturbs EC adaptation to the inflammatory environment, leading to vascular disorders such as atherosclerosis and pathological angiogenesis. Recent work has highlighted the contribution of the calpain-calpastatin stress-responsive intracellular proteolytic system to adaptation failure in ECs. In this review, we summarize our current knowledge of calpain-calpastatin-mediated physiologic and pathogenic regulation in ECs and discuss the molecular basis by which disruption of this system perturbs EC adaptation to the inflammatory environment.